Humanitarian Aid as an Integral Part of the European Union's External Action: The Challenge of Reconciling Coherence and Independence. (13th May 2014) - Orbie, Jan; Van Elsuwege, Peter; Bossuyt, Fabienne
<x xml:space="preserve">Abstract</x> The article focuses on the European Union's (EU) humanitarian aid policy. It addresses the challenge for the EU to deliver independent humanitarian aid while simultaneously seeking to establish more coherence between its external policies. The article examines how the EU tries to reconcile these potentially conflicting policy goals, both de jure and in practice. Empirically, it explores the interaction between EU humanitarian aid and development cooperation, the Common Foreign and Security Policy, and trade policy. While the independence of the humanitarian aid delivery is, for the most part, not being undermined, it remains difficult to establish positive synergies with other external policies because of institutional hurdles and legal constraints, as well as political obstacles and operational incompatibilities.